First results of the new endcap TOF commissioning at BESIII. (8th July 2016) - Wu, Z.; Sun, S.; Heng, Y.; Wang, X.; Sun, Y.; Li, C.; Liu, Z.; Dai, H.; Zhang, J.; Cao, P.; Sun, W.; Wang, S.; et al.
Abstract: The upgrade of the current BESIII Endcap TOF (ETOF) is carried out with Multi-gap Resistive Plate Chamber (MRPC) technology. The installation of the new ETOF has been finished in October 2015. The first results of the MRPCs commissioning at BESIII are reported in this paper.